Genetic Polymorphism of PRL and PRDM16 Genes in Synthetic Backyard Poultry Birds Popular in Andhra Pradesh - Sruthi, Oguru Sai; Devi, Kopparthi Sakunthala; Sudhakar, Kroviddi; Kumar, Kamisetty Aswani (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
A total 317 synthetic backyard poultry birds namely Rajasri, Vanaraja, Native chicken, Commercial layer (BV-300) and broiler (COBB-400)  were randomly selected for determining the genetic polymorphism of PRL and PRDM16 genes using PCR-RFLP method. The restriction  fragment sizes of 160, 144, 81, 54 bp (4 bands), 304, 160, 144, 81, 54 bp (5 bands) and 304, 81, 54 bp (3 bands) were observed for PRL/ Alu1 and 157, 313 bp (2 bands), 470, 313, 144 bp (3 bands) and an uncut fragment of 470 bp for PRDM16/Bgl1 locus. For PRL gene the  genotypic and allelic frequencies of CC, CT, TT and C, T were found to be 0.07, 0.37, 0.56 and 0.26, 0.74 (Rajasri); 0.41, 0.59, 0.00 and 0.70,  0.30 (Commercial layer); 0.16, 0.56, 0.28 and 0.44, 0.56 (Native chicken). For PRDM16 gene they were found to be 0.46, 0.46, 0.08 and  0.69, 0.31 (Vanaraja); 0.51, 0.43, 0.06 and 0.73, 0.27 (Commercial broiler); 0.50, 0.46, 0.04 and 0.73, 0.27 (Native chicken). The observed  (Ho) and expected heterozygosity (He) values ranged from 0.37 to 0.59 ; 0.38 to 0.49 for PRL and 0.43 to 0.46;0.39 to 0.42 for PRDM16 genes. Chi-square differences in genotypic and allelic frequencies at PRL/AluI locus showed significant differences (p≤0.01) between  Rajasri, Commercial layer (BV-300) and Native chicken.
Keywords: Backyard poultry birds; Genetic polymorphism; PRDM16; PRL